Nature as the Chief Architect of the Yakut Arctic - Анастасия Холявко; Алексей Козьмин (Проект Байкал)
The article reveals the peculiarities of nature and climate that influence the way of life in the Arctic settlements of Tiksi and Naiba located in the north-east of Yakutia. The authors propose their ideas for finding new architectural solutions in the Arctic.